Water and ion transport in ocular tissues - Candia, Oscar A. (2006)
Ion-coupled fluid secretion (or absorption) is a property of epithelia, in general, and such fluid transport has been demonstrated with all ocular tissues examined to date, which include corneal endothelium and epithelium, and the epithelia of the ciliary body, lens, and conjunctiva, as well as, the retinal pigmented epithelium.